Playing, Moving, and Thinking: Game-Based Outdoor Learning to Mathematical Problem-Solving Ability - Rani Puspita Sari; Sofnidar Sofnidar; Khairul Anwar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The low level of students’ mathematical problem-solving ability, particularly in learning linear equations in one variable, is influenced by monotonous conventional instruction, making it necessary to adopt a more effective and engaging learning approach to improve this ability. However, empirical studies examining the implementation of game-based outdoor learning to enhance mathematical problem-solving ability in linear equations in one variable at the junior high school level remain limited. Accordingly, this study aims to examine the improvement in mathematical problem-solving ability of VIII students after the implementation of game-based outdoor learning. The research participants were 24 students of class VIII B at a junior high school in Jambi City, selected using a cluster random sampling technique. This study adopted a quantitative descriptive method with a pre-experimental One-Group Pretest–Posttest Design. Students’ improvement in mathematical problem-solving ability was analyzed using N-gain, which was classified into high, moderate, and low categories. Based on the N-gain analysis, of the 24 students involved, 4 students showed a high level of improvement, 14 students demonstrated moderate improvement, and 6 students exhibited low improvement in mathematical problem-solving ability These findings contribute empirical evidence supporting the implementation of game-based outdoor learning to improve junior high school students’ mathematical problem-solving ability in linear equations in one variable.